Subjectivity (Re)visited: A Corpus Study of English Forward Causal Connectives in Different Domains of Spoken and Written Language. Issue 3 (16th March 2021) - Andersson, Marta; Sundberg, Rolf
ABSTRACT: Through a structured examination of four English causal discourse connectives, our article tackles a gap in the existing research, which focuses mainly on written language production, and entirely lacks attests on English spoken discourse. Given the alleged general nature of English connectives commonly emphasized in the literature, the underlying question of our investigation is the potential role of the connective phrases in marking the basic conceptual distinction between objective and subjective causal event types. To this end, our study combines a traditional corpus analysis with 'predictive' statistical modeling for subjectivity variables to investigate whether and how the tendencies found in the corpus depend on the systematic preferences of the language user to encode subjectivity via a discourse connective. Our findings suggest that while certain conceptual structures are quite fundamental to the usages of English connectives, the connectives per se do not seem to have a steady part in categorization of causal events. Rather, their role pertains to the level of intended explicitness bound to specific rhetorical purposes and contexts of use.